Partitioning, repressing and derepressing: dynamic regulations in MLA immune receptor triggered defense signaling - Chang, Cheng; Zhang, Ling; Shen, Qian-Hua (Frontiers in Plant Science, 2013)
Plants and animals have evolved intracellular nucleotide-binding (NB) domain and leucine-rich repeat (LRR)-containing immune receptors (NLRs) to perceive non-self and trigger immune responses. Plant NLRs detect strain-specific pathogen effectors and activate immune signaling leading to extensive transcriptional reprogramming and termination of pathogen infection. Here we review the recent findings in barley MLA immune receptor mediated immune responses against the barley powdery mildew fungus. We focus on nucleocytoplasmic partitioning of immune receptor, bifurcation of immune signaling, transcriptional repression and derepression connecting receptor activation to immune responses. We also discuss similar findings from other plant NLRs where appropriate.